1993
DOI: 10.1090/s0273-0979-1993-00397-5
|View full text |Cite
|
Sign up to set email alerts
|

Quasipositivity as an obstruction to sliceness

Abstract: Abstract. For an oriented link L C S3 = dD4 , let Xs(L) be the greatest Euler characteristic x(F) of an oriented 2-manifold F (without closed components) smoothly embedded in D4 with boundary L . A knot K is slice if Xs(K) = 1 . Realize D4 in C2 as {(z, w) : \z\2 + \w\2 < 1} . It has been conjectured that, if V is a nonsingular complex plane curve transverse to S3 , then Xs(VnS3) = ^(KnZ)4). Kronheimer and Mrowka have proved this conjecture in the case that V n D4 is the Milnor fiber of a singularity. I explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(200 citation statements)
references
References 25 publications
6
194
0
Order By: Relevance
“…Lee and Wilczynski [17] have shown that the lower bounds proved in [8], [20] are realized by topologically locally flat surfaces, for all d which are even or powers of an odd prime. There were earlier counterexamples to the topologically locally flat version of the Thom conjecture, due to Rudolph [21]; see also [22]. It follows from Theorem 1-1 that some of these are not smoothable, cf.…”
Section: Gv)>\$?-o-(x)\-b 2 (X)mentioning
confidence: 96%
See 1 more Smart Citation
“…Lee and Wilczynski [17] have shown that the lower bounds proved in [8], [20] are realized by topologically locally flat surfaces, for all d which are even or powers of an odd prime. There were earlier counterexamples to the topologically locally flat version of the Thom conjecture, due to Rudolph [21]; see also [22]. It follows from Theorem 1-1 that some of these are not smoothable, cf.…”
Section: Gv)>\$?-o-(x)\-b 2 (X)mentioning
confidence: 96%
“…By Theorem 1-1, this is not smoothable for d = 6. In [22], there is an example of a topologically locally flat embedding of a surface of genus 5 representing 5 times the generator of H 2 (CP 2 ,Z), which has geometric intersection number 5 with a complex line. This, too, cannot be smoothable, since by replacing the intersection points with handles, one would obtain an embedded surface of degree 6 and genus 9, contradicting Theorem 1-1.…”
Section: A Lower Bound On the Genera Of Embedded Surfacesmentioning
confidence: 99%
“…This result has been improved in many ways, related to classical link invariants such as genus [1,15], polynomials [11,14], or other invariants such as Khovanov homology [12], knot Floer homology [13] and so on. However they are not essential in this paper and we omit the detail.…”
Section: Basic Notionsmentioning
confidence: 99%
“…We shall call it the Bennequin unknotting inequality. In [15], by using a result of Kronheimer and Mrowka [9], [10], Rudolph showed the slice-Bennequin inequality,…”
Section: The Bennequin Unknotting Inequalitymentioning
confidence: 99%